Exploring atitudes towards immigrants in Cape Town, South Africa - Murambiwa, Rutendo (Department of Social Development, 2015)
Earlier studies conducted in South Africa suggest that negative attitudes towards immigrants are widespread and driven by resource strain, issues around national identity, and the process of ‘othering’. This study uses data from the fifth wave of the Cape Area Panel Study, with a representative sample of young adults (n=2915), in order to explore attitudes towards immigrants in Cape Town. Using a series of vignettes, that is, descriptions of situations in which the details are varied systematically, the researcher examines the extent to which the nationality and individual circumstances of immigrants affect support for deportation or the legitimacy of illegal direct action against them.